From ‘The Letter with Blood Is Learned’ to ‘The Misalignment of Authority’: Socio-Historical Overview of School Authority in Chile; [de “La Letra Con Sangre Entra” Al “Desalineamiento de la Autoridad”: Balance Sociohistórico de la Autoridad Escolar en Chile] - Araujo-Kakiuchi, K (Pontificia Universidad Catolica de Chile, 2024)
In recent decades, the phenomenon of authority has increasingly become a relevant topic in public and academic discussions. This article participates in this discussion by offering a broad interpretation of the evolution of authority in the Chilean school, the sociohistorical transformations to which it has been subjected and what these have implied for its current exercise. In this regard, this paper argues, based on the results of a set of empirical research, that the contemporary difficulties faced by the school authority are associated with a misalignment of the historical matrix developed in the 19th and 20th centuries, the one that supported a ‘naturalized’ normative version of hierarchies, established a vertical framework of management of asymmetries of power and promoted a rote type of obedience. It is precisely in the misalignment between these normative, reglementary and practical orders, as well as in the lack of new models that enable an efficient and conciliated (non-authoritarian) exercise of authority, where one of the main tensions lies, generally expressed through the dominant image of a ‘crisis of authority’ at schools. © 2024 PEL